2019
DOI: 10.3389/fsurg.2019.00015
|View full text |Cite
|
Sign up to set email alerts
|

What Do We Know About the Chevrel Technique in Ventral Incisional Hernia Repair?

Abstract: Introduction: In publications on ventral incisional hernia repair, the Chevrel technique and the onlay operation are often equated. This present review now aims to present the difference between these surgical techniques and analyze the findings available on the Chevrel technique. Materials and Methods: A systematic search of the available literature was performed in January 2019 using Medline, PubMed, Scopus, Embase, Springer Link, and the Cochrane Library, as well as a sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
0
3
0
1
Order By: Relevance
“…Claus et al reported that the subcutaneous onlay laparoscopic approach, also called the SCOLA, was a safe, reproducible, and effective alternative for minimally invasive surgery for patients with abdominal wall hernias associated with a rectus diastasis [ 17 ]. However, such onlay repairs require subcutaneous undermining, which leads to reduced perfusion of the skin flaps, resulting in wound complications including surgical site infections, seromas, and skin necrosis [ 18 ]. For morbidly obese patients, Oleck et al suggested that sparing the epigastric artery perforator was key to reducing the risk of postoperative wound complications in open ventral hernia repair for patients with a BMI of greater than or equal to 40 kg/m 2 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Claus et al reported that the subcutaneous onlay laparoscopic approach, also called the SCOLA, was a safe, reproducible, and effective alternative for minimally invasive surgery for patients with abdominal wall hernias associated with a rectus diastasis [ 17 ]. However, such onlay repairs require subcutaneous undermining, which leads to reduced perfusion of the skin flaps, resulting in wound complications including surgical site infections, seromas, and skin necrosis [ 18 ]. For morbidly obese patients, Oleck et al suggested that sparing the epigastric artery perforator was key to reducing the risk of postoperative wound complications in open ventral hernia repair for patients with a BMI of greater than or equal to 40 kg/m 2 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among these methods, the component separation technique has necessitated the addition of single-and doublemesh placements because the technique created new weak spots and was associated with increased postoperative morbidity. The addition of mesh placement resulted in reduced morbidity and recurrence rates [7,12]. The Expert Consensus Guided by Systematic Review has stated that the use of IPOM may be beneficial in the repair of large incisional hernias [13].…”
Section: Discussionmentioning
confidence: 99%
“…The two techniques differ in operative details: in Chevrel's technique, the defect is closed with sliding myofascial flaps obtained from incision of the anterior layers of rectus sheaths (18). A common feature of both techniques is placement of the mesh in the onlay position on the fascia (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). Previous studies reported a high wound complication rate after the original Chevrel's technique as well as for the other onlay techniques that include skin necrosis, seroma formation and wound infection, which was attributed to the extensive subcutaneous dissection to facilitate overlap of the mesh beyond the lateral border of the rectus abdominis muscles.…”
Section: Discussionmentioning
confidence: 99%